Missionary Activity of Russian Orthodox Church in the Second Half of the XIX - Early XX Centuries (Vyatka province) - E. N. Nemchaninova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The study is devoted to the analysis of the missionary activity of the Russian Orthodox Church in the second half of the XIX - early XX centuries in the context of the history of church-state relations of the period. An attempt is made to classify the key problems of missionary activity based on an analysis of its leading areas using a regional approach. Based on archival documents (primarily the reports of Vyatka bishops and governors), the main problems of the missionary activity of the Russian Orthodox Church in the vast Vyatka province, which is one of the largest in empire in terms of population are analyzed in the paper. The authors proceed from the position that the organization of missionary activity was an important element in ensuring the unity of the state in the period under review, and in this regard consolidated the interests of secular and spiritual authorities both at the central and regional levels. The range and content of the problems of missionary activity, according to the authors, were largely determined by the specifics of the national and confessional composition of the population of the region, the nature of its settlement, as well as unique models of church-state relations that developed at the local level.